2013
DOI: 10.1002/cncr.28015
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of p16 expression and alcohol consumption in Japanese patients with oropharyngeal squamous cell carcinoma

Abstract: BACKGROUND:The prevalence and prognostic value of human papillomavirus-related oropharyngeal squamous cell carcinoma (OPSCC) in Japan has not been evaluated. METHODS: Over a 12-year period, the authors used immunohistochemistry to evaluate the expression of p16 (a cyclin-dependent kinase inhibitor and tumor suppressor) in samples from 173 patients with OPSCC at a single institution and to determine its prevalence and influence on disease prognosis. RESULTS: The prevalence of p16-positive OPSCC was 33.7% in ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 26 publications
(57 reference statements)
2
39
2
Order By: Relevance
“…Actually, HPV status was examined in 25 patients in 2 institutions; however, only 2 patients (8%) were found to be HPV‐positive. According to other reports, the HPV‐positive rate has been rising sharply in recent years . However, cisplatin has been and will continue to be the most important key drug for the treatment of patients with oropharyngeal SCC, despite the introduction of molecular‐targeted agents for the treatment of oropharyngeal SCC and the increase in HPV‐related oropharyngeal SCC, which has a better prognosis than HPV‐negative oropharyngeal SCC .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, HPV status was examined in 25 patients in 2 institutions; however, only 2 patients (8%) were found to be HPV‐positive. According to other reports, the HPV‐positive rate has been rising sharply in recent years . However, cisplatin has been and will continue to be the most important key drug for the treatment of patients with oropharyngeal SCC, despite the introduction of molecular‐targeted agents for the treatment of oropharyngeal SCC and the increase in HPV‐related oropharyngeal SCC, which has a better prognosis than HPV‐negative oropharyngeal SCC .…”
Section: Discussionmentioning
confidence: 99%
“…In the present cases, a solid tumor grew within the palatine tonsil, which was covered with normal mucosa and showed a minute mucosal defect. Recently, the incidence of HPV‐related oropharyngeal cancer has been increasing; thus, a considerable number of patients showing similar clinical features, such as a minor mucosal defect on the surface of the palatine tonsil, may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies from the 1990s suggested that approximately 50% of OSCC were associated with HPV, whereas more recent studies have suggested that HPV association may account for up to 70-80% of cases in North America and Europe [11,12]. In Asia, the prevalence has been reported to be 30-50% [13,14]. Therefore, a regional difference in the prevalence of HPV-associated OSCC exists.…”
Section: Discussionmentioning
confidence: 99%
“…In our retrospective study, the exact number of patients with a primary site in the oropharynx was unknown because some occult primary sites may have been controlled without detection because of the application of postoperative radiotherapy. However, this ratio was higher than that of p16 overexpression in Asian OSCC patients (30-50%) [13,14]. A presenting feature of HPV-associated OSCC is the abrupt appearance of an enlarged cervical lymph node and small primary lesion [17,18].…”
Section: Discussionmentioning
confidence: 99%